Artesunate Alleviates Paclitaxel-Induced Neuropathic Pain in Mice by Decreasing Metabotropic Glutamate Receptor 5 Activity and Neuroinflammation in Primary Sensory Neurons - Li, Yize; Kang, Jiamin; Xu, Ying; Li, Nan; Jiao, Yang; Wang, Chenxu; Wang, Chunyan; Wang, Guolin; Yu, Yonghao; Yuan, Jingjing; Zhang, Linlin (Frontiers in Molecular Neuroscience, 2022)
Experimental studies on the pathogenetic process of paclitaxel-induced neuropathic pain (PINP) have been initially carried out, but PINP still has no effective therapy. Recently reported studies have highlighted the involvement of glutamate receptors and neuroinflammation in peripheral and central nociceptive transmission in PINP. Artesunate is a first-line antimalarial drug with established efficacy in alleviating pain in a variety of pathologies. The current work assessed whether artesunate inhibited PINP by modulating metabotropic glutamate receptor 5 (mGluR5) and neuroinflammation in mice. The analgesic effect of artesunate was verified by assessing the mechanical frequency of paw withdrawal and thermal latency of paw withdrawal as well as spontaneous pain. The expression levels of mGluR5, pain-related receptors and neuroinflammatory markers in dorsal root ganglia (DRG) were examined. In addition, treatment with CHPG and MPEP (mGluR5 agonist and antagonist, respectively) was performed to determine mGluR5’s role in the analgesic properties of artesunate. We demonstrated artesunate prevented PINP in a dose-dependent manner, while exerting a clear analgesic effect on already existing PINP. Artesunate normalized paclitaxel-related expression changes in DRG mGluR5, NR1 and GluA2, as well as six paclitaxel related neuroinflammation markers. Intrathecal application of MPEP treated PINP by reversing NR1 and GluA2 expression changes but had no effects on chemokines and inflammatory factors. Furthermore, artesunate treatment reversed acute pain following CHPG application. In conclusion, this study revealed that artesunate alleviates paclitaxel-induced hyperalgesia and spontaneous pain by decreasing DRG mGluR5 expression and neuroinflammation in the mouse model of PINP.